Analysis of International Relations Theory Toward the Prospective Foreign Policy in the Vision and Mission of Indonesian Presidential Candidates 2024 - Sally, Novian Uticha; Orwela, Citra (POLITEA, 2023)
As the national election in Indonesia is drawing close, the political competition done by each of presidential and vice-presidential candidates is getting massive. The year 2023 becomes pivotal for the candidates to show case their potential and attention to the significant issues. In the same year, a lot has happened in the international sphere that influences Indonesian local politics. This article will seek to analyze the political communication used by Indonesian presidential and vice-presidential candidates in their campaign in responding global issues. The research approach used in this research is qualitative approach using comparative analysis techniques. The type of research is library research, in which datum will be collected from vision and mission of presidential candidates. The result shown that all Indonesian presidential candidates have made some agendas pertaining eco-global, cooperation and competition in the international realm.